Representasi Perempuan Dalam Pemberitaan Kekerasan Seksual Pada Koran Kedaulatan Rakyat - Zakiya Fatihatur Rohmah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
News can be used as an advocacy tool to convey support for the elimination of sexual violence. But on one side of the news can also be a cause of sexual violence against women. When the news positions women as the object of the news. That is, women are not given the opportunity to be the subject of the news. Because of that, it is important to see how the mass media represent women from reporting sexual violence?. The news analyzed is the February 2019 edition of the daily Kedaulatan Rakyat using Sara Mills's discourse analysis. The edition was chosen because in one of his reports contained the Agni case, UGM students who experience sexual violence. The results of the study show two things. First, the position as the subject of the news is dominated by men represented by the campus and the police. Second, the media ideology of the Daily Kedaulatan Rakyat is a patriarchal ideology, that is, positioning men is higher than women.